2018
DOI: 10.1101/313494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An ancestral role of pericentrin in centriole formation through SAS-6 recruitment

Abstract: Short summaryThe pericentriolar matrix (PCM) is not only important for microtubule-nucleation but also can regulate centriole biogenesis. Ito et al. reveal an ancestral interaction between the centriole protein SAS-6 and the PCM component pericentrin, which regulates centriole biogenesis and elongation. AbstractThe centrosome is composed of two centrioles surrounded by a microtubule-nucleating pericentriolar matrix (PCM). Centrioles regulate matrix assembly. Here we ask whether the matrix also regulates centri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…We searched for orthologues of components of the human centrosome localizing to centrioles and PCM and the fission yeast SPB components by using reciprocal pairwise sequence-based (BLASTP and phmmer) and domain-based (hmmsearch) methods [ 87 , 88 ]. Black circles represent the presence of orthologues; blue circles indicate that previous studies showed the presence of a protein with short conserved motifs [ 47 , 56 , 60 ] although we failed to identify it by the above-mentioned computational methods; white circles indicate no detectable orthologue ([ 89 ] and our unpublished results).…”
Section: Figurementioning
confidence: 84%
“…We searched for orthologues of components of the human centrosome localizing to centrioles and PCM and the fission yeast SPB components by using reciprocal pairwise sequence-based (BLASTP and phmmer) and domain-based (hmmsearch) methods [ 87 , 88 ]. Black circles represent the presence of orthologues; blue circles indicate that previous studies showed the presence of a protein with short conserved motifs [ 47 , 56 , 60 ] although we failed to identify it by the above-mentioned computational methods; white circles indicate no detectable orthologue ([ 89 ] and our unpublished results).…”
Section: Figurementioning
confidence: 84%
“…Overexpression of Pericentrin leads to overduplication of centrioles in human transformed cells 27 . More recently, Pericentrin was shown to recruit Sas6 and to be involved in centriole biogenesis and stability in drosophila 28,29 . The increasing expression of Pericentrin during A-phase, visible by the increasing surface of the Pericentrin cloud, may be involved in the sequential formation of procentrioles we observed, even in the absence of centrosomal centrioles.…”
Section: Discussionmentioning
confidence: 99%